2021
DOI: 10.1016/j.clinthera.2021.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ivermectin in Patients With COVID-19: A Multicenter, Double-blind, Randomized, Controlled Clinical Trial

Abstract: Purpose: Given the coronavirus disease 2019 (COVID-19) pandemic, there is a global urgency to discover an effective treatment for patients withthis disease. This study aimed to evaluate the effects of the widely used antiparasitic drug ivermectin on outcomes in patients with COVID-19.Methods: In this randomized, double-blind clinical trial, patients with COVID-19 admitted to 2 referral tertiary hospitals in Mazandaran, Iran, were randomly divided into 2 groups: intervention and control. In addition to standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 31 publications
1
52
2
1
Order By: Relevance
“…AIIMS-Patna is the highest referral institute in the state of Bihar for not only COVID-19 but for any medical or surgical condition owing to its state-ofthe-art facilities and trained healthcare staff. An Iranian RCT by Shahbaznejad et al (27) reported significantly lower duration of hospital stay [median ± standard error (SE): 6.0 ± 0.5 days)] in patients treated with single enteral dose of ivermectin compared to the placebo group [Median ± SE: 7.0 ± 0.4 days)] which was discordant to our observations. ICU support requirement were found to be similar in both the groups (9.1% in ivermectin group vs. 10.5% in placebo group) in the present study.…”
Section: Discussionsupporting
confidence: 64%
“…AIIMS-Patna is the highest referral institute in the state of Bihar for not only COVID-19 but for any medical or surgical condition owing to its state-ofthe-art facilities and trained healthcare staff. An Iranian RCT by Shahbaznejad et al (27) reported significantly lower duration of hospital stay [median ± standard error (SE): 6.0 ± 0.5 days)] in patients treated with single enteral dose of ivermectin compared to the placebo group [Median ± SE: 7.0 ± 0.4 days)] which was discordant to our observations. ICU support requirement were found to be similar in both the groups (9.1% in ivermectin group vs. 10.5% in placebo group) in the present study.…”
Section: Discussionsupporting
confidence: 64%
“…IVM has been tested in more than 20 randomized controlled trials (RCTs) for COVID-19 treatment, with statistically highly significant clinical benefits in almost all of these and a pooled mortality reduction of 78% for the treatment vs. control groups [5]. Five such studies for IVM treatment of COVID-19 recently published in top-tier medical journals have all shown multiple clinical benefits for IVM vs. controls, most of these with high statistical significance on the order of p < 0.002 [6][7][8][9][10]. IVM is well tolerated at much greater than the standard single dose of 200 μg/kg [11,12] and has been used in RCTs for COVID-19 treatment at cumulative doses of 1,500 μg/kg [13], 1,600 μg/kg [14], and 3,000 μg/kg [15] over 4 or 5 days either without or with mild and transient adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…There was, however, some variation in the regimes used by these studies. Although the effect on viral clearance is not con rmed, there were many studies that reported a signi cant reduction in the time to recovery in the ivermectin group as compared to the control group [19][20][21]. Even when used to treat severe COVID-19 patients, ivermectin can provide an increase in clinical recovery, improvement in prognostic laboratory parameters, and a decrease in mortality rates [22].…”
Section: Discussionmentioning
confidence: 99%